PSORIASIS AS A MANIFESTATION OF AN UNDIAGNOSED HIV INFECTION. CASE REPORT. - Juliana Lopes; Fernanda Almeida (Sociedade Galega de Medicina Interna, 2018)
The prevalence of psoriasis in HIV disease has been reported to be the same as that in the general population, occurring in approximately 1-3% of HIV-positive individuals. 1,2 The clinical manifestations of psoriasis observed in HIV-infected individuals are similar to those in non-HIV-infected individuals with some variations, but the clinical behavior of psoriasis appear to be different. These patients responds poorly to treatment and have a high morbidity rate, thus posing a challenge to clinicians. We present a case of severe psoriasis associated with an undiagnosed HIV infection, with no response to classic therapy that improved after initial ART (Anti Retroviral Therapy).